2018
DOI: 10.3892/mmr.2018.8488
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Fuzi protects against Ox‑LDL‑induced calcification of human vascular smooth muscle cells by increasing autophagic activity

Abstract: Polysaccharide from Fuzi (FPS) is a water-soluble polysaccharide isolated from the traditional Chinese herbal medicine Fuzi. It has been demonstrated to protect hepatocytes against ischemia-reperfusion injury through its potent antioxidant effects, and to attenuate starvation-induced cytotoxicity in H9c2 cells by increasing autophagic activity. In the present study, Alizarin Red S staining was used to detect mineral deposition and reverse transcription-quantitative polymerase chain reaction was used to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The expression of VSMC differentiation marker genes, including smooth muscle 22α (SM22α) and smooth muscle α-actin (SMα-actin), is decreased during the smooth muscle cell phenotypic transition (10). Meanwhile, Runt-related transcription factor 2 (Runx2; also known as core binding factor α-1, cbfα-1), an important osteoblast-specific gene that regulates osteoblast and chondrocyte differentiation, is expressed in VC (1113).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of VSMC differentiation marker genes, including smooth muscle 22α (SM22α) and smooth muscle α-actin (SMα-actin), is decreased during the smooth muscle cell phenotypic transition (10). Meanwhile, Runt-related transcription factor 2 (Runx2; also known as core binding factor α-1, cbfα-1), an important osteoblast-specific gene that regulates osteoblast and chondrocyte differentiation, is expressed in VC (1113).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, intermittent administration of valproic acid did not ameliorate VCN [ 63 ]. Furthermore, FPS attenuated ox-LDL-induced VSMC calcification in vitro [ 64 ]. The authors stated that the protective effects of FPS on VCN are due to its ability to increase autophagy, characterized by an increased LC3-II/LC3-I ratio and decreased p62 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies confirmed that 3-MA aggravates VSMC calcification [ 52 , 53 , 72 ]. Furthermore, multiple studies added 3-MA, in combination with an autophagy, inducing pharmacological intervention, thereby showing that 3-MA abolishes the beneficial effects of autophagy induction on VCN [ 59 , 61 , 64 , 66 , 67 ]. Additionally, CD137 activation led to JNK-mediated disrupted autophagic flux and aggravated VCN [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified five types of potential antioxidants with therapeutic effects against VC based on the literature search, including linalool 61 , lipoic acid 2224 , rosmarinic acid 63 , fermentation broth extracts from Actinobacteria 59 , and polysaccharide from Fuzi product 60 . Two (40%) of them have ROS scavenging ability, while the other three (60%) do not (Fig.…”
Section: Antioxidants From Natural Non-dietary Sourcesmentioning
confidence: 99%
“…Finally, extracts of bacterial and plant products are also found to counteract VC experimentally. Preliminary results from Liao et al showed that polysaccharide extracted from Radix Aconiti Carmichaeli , a raw product with anti-oxidant activity, could reduce calcification severity of ox-LDL-treated VSMCs, partially by activating autophagy 60 . Salimi et al also found that metabolites extracted from cultured Nocardia strain could attenuate protein oxidation, reduce inflammation, and reduce VSMC calcification severity 59 .…”
Section: Antioxidants From Natural Non-dietary Sourcesmentioning
confidence: 99%